Establishment of a resilient modulus test for evaluating reduced size asphalt mixture - Anthoney, Francis Xavier (2019)
The distress in asphalt pavements, which includes fatigue, rutting, and lowtemperature cracking, were all related to the elastic modulus of the asphalt layer. The elastic modulus of the asphalt layer is interchangeably used with resilient modulus. Besides, the elastic modulus of asphalt concrete is a design variable for asphalt pavement structural design when the elastic-layer system theory is employed. However, in the most commonly used asphalt concrete design methods such as the Marshall, Hveem, and Superpave methods, the elastic modulus is not used as a control variable. Thus, the elastic modulus of asphalt concrete might not have studied. In current practice, the performance evaluation of existing flexible pavements has become a priority issue for many highway maintenance engineers. To make appropriate rehabilitation and management decisions, the engineers most often rely on efficient methods for the determination of the strength of pavement layers. This statement underlined that the resilient modulus is a crucial parameter to be identified and should be used in pavement design. The resilient modulus of asphalt mixtures is typically measured using the indirect tension test procedure in compliance with the ASTM D4123 standard. The scope of this study is limited to the binder with penetration grade 80/100 Hot Mix Asphalt (HMA) pavements. The coarse and fine aggregate, together with mineral fillers conforming to the gradation envelope for asphalt concrete with a nominal aggregate size of 14mm from JKR Standard Specification for roadworks reference JKR/SPJ/2008-S4 has been adopted. The small size of asphalt mixture specimens was prepared and studied in the laboratory, and the effects of different loading and pulse widths applied to 225 numbers of samples were investigated. In the mix design stage, a total of 20 numbers of samples were prepared using Marshall Mix Design, which consists of 15 compacted samples and the remaining five loose samples for Theoretical Maximum Density (TMD). The standard requirement is that the prepared specimens for the tests should have a minimum height of the sample over its diameter ratio of 0.4. Generally, specimens used in the tests are either a nominal 100mm or 150mm in diameter, with a minimum thickness over a diameter ratio of 0.4. However, 100 mm diameter core specimens taken from site wearing courses with thicknesses from 40 mm to 50 mm most often do not fulfil the minimum ratio of 0.4 after the samples are trimmed for testing. Since there was not an option, part of the binder courses was trimmed to make up the requirement. This tends to result in an inaccurate assessment of the resilient modulus values of the samples. As such, a new procedure was developed to test specimens smaller than 100 mm in diameter. This may minimize the material volume requirement from the field and also for the fabrication of smaller samples in the laboratory. Based on the available thickness of wearing course or overlay, the appropriate sizes were determined. For a two-layer system, 56.3 mm diameter was significantly necessary, while a 37.5 mm diameter was observed to be appropriate for a three-layer system. Resilient modulus test using reduced size specimens of 56.3mm and 37.5mm in diameter has excellent potential for application in the industry.